Open distance learning course “Curator of content”: experience - Yu. M. Glavcheva; V. M. Kukharenko (CTE Workshop Proceedings, 2015)
Research goal: to analyze of the experience of STU “KhPI” on carrying out of Open distance learning course. Research objectives: to teach the information specialist of the new direction – “Curator of content” or Network information analyst. Object of research: Open distance learning course "Curator of content". Subject of research: the experience of on carrying out of Open distance learning course "Curator of content". Research methods used: analysis of state standards, statistics and publications. Results of the research. The competence of such specialist includes the skills of search and information services for aggregation, filtering, storage, processing and distribution of information. The course has to develop, improve, takes into consideration the development of information technology and various application areas: education and science (support of vocational, educational and technological activity of academicians), business (marketing), librarianship and others. Conclusions: the relevance of subject of course is testified by a great number of those who wish to study the course.